1990
DOI: 10.1210/jcem-70-2-467
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Osteocalcin Fragments in Human Urine and Serum as Detected by a Midmolecule Osteocalcin Radioimmunoassay*

Abstract: Reliable markers of bone formation are essential to the investigation of metabolic bone disorders. In this regard, evidence indicates that circulating levels of human osteocalcin (OC) correlate with the skeletal isoenzyme of alkaline phosphatase and can be used as an index of bone formation. A disadvantage of using serum OC as a marker of formation is its diurnal variation. To address this problem we carried out our studies to determine the usefulness of urine in the assessment of bone turnover. Using a midmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…However, later studies on patients with different metabolic bone diseases have suggested that not all of osteocalcin fragments are derived from the metabolism of osteocalcin in the circulation or peripheral organs but also from osteocalcin embedded in bone (21)(22)(23). Thus, part of osteocalcin found in the blood may also originate from the resorption process, when osteocalcin embedded in the bone matrix is released during bone degradation (Fig.…”
Section: Osteocalcin (Oc)mentioning
confidence: 99%
“…However, later studies on patients with different metabolic bone diseases have suggested that not all of osteocalcin fragments are derived from the metabolism of osteocalcin in the circulation or peripheral organs but also from osteocalcin embedded in bone (21)(22)(23). Thus, part of osteocalcin found in the blood may also originate from the resorption process, when osteocalcin embedded in the bone matrix is released during bone degradation (Fig.…”
Section: Osteocalcin (Oc)mentioning
confidence: 99%
“…Circulating osteocalcin (OC), a bone-specific protein produced by osteoblasts, is widely used as an index of bone formation (3,4 ). Fragments of OC are also found in urine (5)(6)(7), and the measurement of urinary OC (U-OC) is another method for monitoring bone metabolism (8 -11 ). We recently described 3 immunoassays for measuring U-OC (11 ).…”
Section: Urinary Osteocalcin Is a Useful Marker Formentioning
confidence: 99%
“…Increased serum PDGF concentrations during and after hemodialysis, attributable to PLT-membrane contact at artificial surfaces, may be directly involved in the increased frequency of atherosclerosis in hemodialysis patients (2 ). The role of circulating GFs in many other nonmalignant clinical conditions has also been investigated (3)(4)(5)(6)(7)(8).…”
Section: Urinary Osteocalcin Is a Useful Marker Formentioning
confidence: 99%
“…The BGP molecules, after cleavage of the propeptide, are partly released into the peripheral circulation and can be detected in serum or plasma by RIA [45][46][47]. But previous reports have demonstrated that the majority of their fragments, which derive from the processing during bone resorption, are also released into the circulation and that former RIAs for BGP cross-react with the fragments [48][49][50]. Consequently, osteoblastic bone formation could be evaluated by using a specific assay system to detect intact molecular BGP.…”
Section: Discussionmentioning
confidence: 99%